2003
DOI: 10.1079/bjn2002765
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated linoleic acid decreases fat accretion in pigs: evaluation by dual-energy X-ray absorptiometry

Abstract: Thirty female Large White £ Landrace pigs (average weight 57·2 (SD 1·9) kg) were allocated to one of six dietary treatments containing 0, 1·25, 2·5, 5·0, 7·5 or 10·0 g 55 % conjugated linoleic acids (CLA) isomers (CLA-55)/kg diet and fed for 8 weeks. Each pig was scanned at 0, 28 and 56 d and again at post slaughter using dual-energy X-ray absorptiometry (DXA) to determine the temporal pattern of body composition responses. Values determined by DXA were adjusted using regression equations generated from valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
61
1
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 33 publications
7
61
1
7
Order By: Relevance
“…Because leptin is secreted mainly by adipocytes, circulating levels correlate directly with body mass index in humans (Ahima and Flier, 2000), with a positive correlation between circulating leptin levels and adiposity also reported in pigs (Barb et al, 2001). As CLA is reported to reduce body fat content (Ostrowska et al, 2003), a reduction in plasma leptin levels would be expected in CLA-supplemented animals (Kang and Pariza, 2002) unless there is central or peripheral leptin resistance. Leptin, by binding to its receptors located in skeletal muscle and fat cells promotes energy dissipation and prevents fatty acid accumulation in these tissues (Ceddia, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Because leptin is secreted mainly by adipocytes, circulating levels correlate directly with body mass index in humans (Ahima and Flier, 2000), with a positive correlation between circulating leptin levels and adiposity also reported in pigs (Barb et al, 2001). As CLA is reported to reduce body fat content (Ostrowska et al, 2003), a reduction in plasma leptin levels would be expected in CLA-supplemented animals (Kang and Pariza, 2002) unless there is central or peripheral leptin resistance. Leptin, by binding to its receptors located in skeletal muscle and fat cells promotes energy dissipation and prevents fatty acid accumulation in these tissues (Ceddia, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…11,13,15,[21][22][23]37 It has not been established whether CLA continues to offer antiadiposity action over the long-term period in animals or humans. Although no adverse effects of CLA have been observed in pigs, [32][33][34][35][36]39,[41][42][43] fat liver and spleen as well as insulin resistance have been reported in mice after LCA supplementation. 11,12,15,20,38,98,99 Results of these studies have raised a question relevant to humans of whether it is safe to supplement with CLA.…”
Section: Discussionmentioning
confidence: 99%
“…16,32,[34][35][36]39,[41][42][43] It has been reported that back-fat thickness was significantly decreased in male and female pigs supplemented with 2.0% CLA mixture containing 15% c9t11 and 15% t10c12 isomers during the growing-finishing period (24-117 kg). 35 Similarly, Wiegnand et al 36 observed a decrease in fat deposition in growing-finishing (28-115 kg) pigs fed 0.75% CLA mixture containing 27% c9t11 and 20% t10c12 isomers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations